Barrier screens: a method to sample blood-fed and host-seeking exophilic mosquitoes - Burkot Thomas R (Malaria Journal, 2013)
Abstract Background Determining the proportion of blood meals on humans by outdoor-feeding and resting mosquitoes is challenging. This is largely due to the difficulty of finding an adequate and unbiased sample of resting, engorged mosquitoes to enable the identification of host blood meal sources. This is particularly difficult in the south-west Pacific countries of Indonesia, the Solomon Islands and Papua New Guinea where thick vegetation constitutes the primary resting sites for the exophilic mosquitoes that are the primary malaria and filariasis vectors. Methods Barrier screens of shade-cloth netting attached to bamboo poles were constructed between villages and likely areas where mosquitoes might seek blood meals or rest. Flying mosquitoes, obstructed by the barrier screens, would temporarily stop and could then be captured by aspiration at hourly intervals throughout the night. Results In the three countries where this method was evaluated, blood-fed females of Anopheles farauti, Anopheles bancroftii, Anopheles longirostris, Anopheles sundaicus, Anopheles vagus, Anopheles kochi, Anopheles annularis, Anopheles tessellatus, Culex vishnui, Culex quinquefasciatus and Mansonia spp were collected while resting on the barrier screens. In addition, female Anopheles punctulatus and Armigeres spp as well as male An. farauti, Cx. vishnui, Cx. quinquefasciatus and Aedes species were similarly captured. Conclusions Building barrier screens as temporary resting sites in areas where mosquitoes were likely to fly was an extremely time-effective method for collecting an unbiased representative sample of engorged mosquitoes for determining the human blood index.